American Studies - V. O. Pechatnov (Vestnik MGIMO-Universiteta)
The "Founding fathers" of American Studies at MGIMO are considered to be A.V. Efimov and L.I. Clove. Alexey Efimov - Corresponding Member of the USSR Academy of Sciences since 1938, Head of the Department of Modern and Contemporary History and Dean of the Historical School at the Moscow State University - one of the first professors of the Faculty of International Relations MGIMO. Efimov distinguished himself by a broad vision and scope of scientific interests. Back in 1934 he published a monograph "On the history of capitalism in the United States," which initiated a series of research culminating in the fundamental work "The United States. The path of capitalist development (pre-imperialist era)". Alexey was not only a great scientist but also a great teacher, whose lectures was popular throughout Moscow. His lecture courses, given at the end of the 1940s at MGIMO, became the basis for the first post-war history textbooks USA - "Essays on the history of the United States." At least as colorful a figure was Professor Leo Izrailevich Zubok - a man of unusual destiny. As a teenager he emigrated to the United States with his parents, where he soon joined the American revolutionary movement in the 1920s and was forced to leave the country. He came to MGIMO being already an experienced scientists. His research interests were very wide: from the study of American foreign policy expansion to the history of the labor movement in the United States. Zubok's fundamental works still have not lost its scientific significance. He has successfully combined scientific work with teaching. Tutorials that are based on his lectures were very popular not only among students of MGIMO.